Infrared aircraft measurements of stratospheric composition over Antarctica during September 1987 - Toon, G. C.; Farmer, C. B.; Lowes, L. L.; Schaper, P. W.; Blavier, J.-F. (1989)
The Jet Propulsion Laboratory Mark IV interferometer recorded high-resolution, infrared solar spectra from the NASA DC-8 aircraft during flights over Antarctica in September 1987. The atmospheric absorption features in these spectra have been analyzed to determine the burdens of O3, NO, NO2, HNO3, ClNO3, HCl, HF, CO2, CH4, N2O, HCN, CO, H2O, CFCl3, and CF2Cl2. The results show a 'collar' of high HNO3 and ClNO3 surrounding a 'core' in which the burdens of these and of HCl and NO2 are very low. Clear increases in the burdens of HF and HNO3 were observed during the course of September in the vortex core. HCl and NO2 exhibited smaller, less significant increases. The burdens of the tropospheric source gases, N2O, CH4, HCN, CFCl3, CF2Cl2, CO, and H2O, were observed to be much smaller over Antarctica than at midlatitudes. This, together with the fact that HF over Antarctica was more than double its midlatidue value, suggests that downwelling had occurred.